Development of a high-sensitivity radon monitor for a radon calibration system at KRISS. (October 2020) - Hwang, S.H.; Han, M.J.; Seon, Y.G.; Lee, J.M.; Lee, K.B.
Abstract: A radon calibration system is being developed with a high-sensitivity radon detector using electrostatic collection and an alpha spectrometer. Eight radon cells, each with a volume of 1.354 L, are integrated to achieve a high-sensitivity radon monitor with a total detector volume of 10.832 L. The sensitivity is estimated to be 35.6 ± 0.2 (36.8 ± 0.2) times higher relative to the RAD7 radon monitor for the detection of 218 Po ( 214 Po), respectively. Highlights: Development of the electrostatic collection radon detector with eight multi-radon cells. The optimum applied high voltage is found to be -1.3 kV. The FWHM of alpha spectrometry of the decayed products from 222 Rn is estimated to be 91.6 keV for the 218 Po. The relative sensitivity of the KRISS radon detector shows 36.2 times high-sensitivity comparing with the RAD7.